Student challenges in English Medium Instruction (EMI) courses: Insights from an International Student Mobility Program - Nurmala Elmin Simbolon; Nizamuddin Sadiq; Samantha Curle (Universitas Syiah Kuala, 2025)
This study examines the language-related challenges faced by Indonesian students enrolled in short-term English Medium Instruction (EMI) courses abroad, facilitated by the Indonesian International Student Mobility Awards (IISMA). Using a mixed-methods approach, we analyzed survey responses from fifty-four students and conducted three focus group interviews to gain a comprehensive understanding of their experiences. The research instrument, based on Evans and Morrison (2011) and modified by Kamasak et al. (2021), was employed to quantify these challenges. Our analysis revealed significant challenges in writing and speaking. These difficulties were prevalent regardless of the students backgrounds, suggesting that current preparatory measures may be insufficient. Specifically, writing emerged as the most formidable challenge, with many students struggling to express their ideas clearly and coherently in English. These findings underscore the critical need for comprehensive preparatory frameworks that go beyond basic linguistic competence. We advocate for the integration of robust academic preparation programs within mobility initiatives to better equip students for the linguistic demands of EMI courses. Such enhancements are essential for improving the overall academic experience and success of students in international educational contexts. The implications of this study extend to policymakers and educators involved in designing and implementing EMI programs, emphasizing the importance of targeted support to address language-related challenges.